Счастливая семья: [повести и рассказы : 16+] / Маша Трауб - Трауб Маша (Проза Маши Трауб, 2015)
Экземпляры: ф.4 (20151215) / Инвентарный номер: 060093 / Цена: 295.00 / Авт.знак: Т 65 / ГРНТИ: 17.82.30 / ББК: 84(2Рос=Рус)6